Assessing the Delivery of Molecules to the Mitochondrial Matrix Using Click Chemistry. (25th May 2016) - Hoogewijs, Kurt; James, Andrew M.; Smith, Robin A. J.; Gait, Michael J.; Murphy, Michael P.; Lightowlers, Robert N.
Abstract: Mitochondria are central to health and disease, hence there is considerable interest in developing mitochondria‐targeted therapies that require the delivery of peptides or nucleic acid oligomers. However, progress has been impeded by the lack of a measure of mitochondrial import of these molecules. Here, we address this need by quantitatively detecting molecules within the mitochondrial matrix. We used a mitochondria‐ targeted cyclooctyne (MitoOct) that accumulates several‐ hundredfold in the matrix, driven by the membrane potential. There, MitoOct reacts through click chemistry with an azide on the target molecule to form a diagnostic product that can be quantified by mass spectrometry. Because the membrane potential‐dependent MitoOct concentration in the matrix is essential for conjugation, we can now determine definitively whether a putative mitochondrion‐targeted molecule reaches the matrix. This "ClickIn" approach will facilitate development of mitochondria‐targeted therapies. Abstract : Research into the delivery of large polar molecules and their detection in the mitochondrial matrix is held back by the lack of a robust and quantitative measure of import. Here, we demonstrate a mitochondrial matrix‐specific click reaction, forming a diagnostic product that can be quantified by mass spectrometry.